Adrenal Insufficiency in Children With Nephrotic Syndrome on Corticosteroid Treatment - Karmila Abu Bakar; Karmila Abu Bakar; Khairunnisa Khalil; Khairunnisa Khalil; Yam Ngo Lim; Yok Chin Yap; Mirunalini Appadurai; Sangeet Sidhu; Chee Sing Lai; Azriyanti Anuar Zaini; Nurshadia Samingan; Muhammad Yazid Jalaludin (Frontiers Media S.A., 2020)
Background: Adrenal insufficiency can result from impaired functions at all levels of hypothalamic-pituitary-adrenal (HPA) axis. We here studied risk factors associated with adrenal insufficiency in children receiving prolonged exogenous steroid treatment for nephrotic syndrome.Method:We performed low-dose Synacthen tests (LDSTs, 0.5 μg/m2) in children with steroid-sensitive nephrotic syndrome 4-6 weeks after discontinuation of the corticosteroid therapy. We measured early morning serum cortisol levels at baseline and at intervals of 10, 20, 30, and 60 min following the stimulation test. We defined normal HPA axis stimulation responses as those with peak cortisol cut-off values >550 nmol/L.Result:We enrolled 37 children for this study research. All children enrolled had normal early morning cortisol levels. However, 13 (35.1%) demonstrated HPA axis suppression (by LDST) 4-+6 weeks after discontinuation of oral prednisolone. Nephrotic syndrome diagnosed before 5 years of age (OR, 0.75; 95% CI, 0.57-0.99; p = 0.043), and steroid-dependence [OR, 5.58; 95% confidence interval (CI), 1.06-29.34; p = 0.042] were associated with increased risk of developing adrenal suppression after steroid discontinuation.Conclusion:HPA axis suppression, may go unnoticed without proper screening. A normal early morning cortisol level (275-555 nmol/L) does not exclude adrenal insufficiency in children with steroid-sensitive nephrotic syndrome. Further screening with LDSTs, particularly in children younger than 5 years at diagnosis, may be warranted.